Reasons rural Laotians choose home deliveries over delivery at health facilities: a qualitative study - Sychareun, Vanphanom (BioMed Central, 2012)
BACKGROUND: Maternal mortality among poor rural women in the Lao People’s Democratic Republic (Lao PDR) is among the highest in Southeast Asia, in part because only 15% give birth at health facilities. This study explored why women and their families prefer home deliveries to deliveries at health facilities. METHODS: A qualitative study was conducted from December 2008 to February 2009 in two provinces of Lao PDR. Data was collected through eight focus group discussions (FGD) as well as through in-depth interviews with 12 mothers who delivered at home during the last year, eight husbands and eight grandmothers, involving a total of 71 respondents. Content analysis was used to analyze the FGD and interview transcripts. RESULTS: Obstacles to giving birth at health facilities included: (1) Distance to the health facilities and difficulties and costs of getting there; (2) Attitudes, quality of care, and care practices at the health facilities, including a horizontal birth position, episiotomies, lack of privacy, and the presence of male staff; (3) The wish to have family members nearby and the need for women to be close to their other children and the housework; and (4) The wish to follow traditional birth practices such as giving birth in a squatting position and lying on a “hot bed” after delivery. The decision about where to give birth was commonly made by the woman’s husband, mother, mother-in-law or other relatives in consultation with the woman herself. CONCLUSION: This study suggests that the preference in rural Laos for giving birth at home is due to convenience, cost, comfort and tradition. In order to assure safer births and reduce rural Lao PDR’s high maternal mortality rate, health centers could consider accommodating the wishes and traditional practices of many rural Laotians: allowing family in the birthing rooms; allowing traditional practices; and improving attitudes among staff. Traditional birth attendants, women, and their families could be taught and encouraged to recognize the signs of at-risk pregnancies so as to be able to reach health facilities on time.